2012
DOI: 10.1371/journal.pone.0039248
|View full text |Cite
|
Sign up to set email alerts
|

Caspase Inhibitors of the P35 Family Are More Active When Purified from Yeast than Bacteria

Abstract: Many insect viruses express caspase inhibitors of the P35 superfamily, which prevent defensive host apoptosis to enable viral propagation. The prototypical P35 family member, AcP35 from Autographa californica M nucleopolyhedrovirus, has been extensively studied. Bacterially purified AcP35 has been previously shown to inhibit caspases from insect, mammalian and nematode species. This inhibition occurs via a pseudosubstrate mechanism involving caspase-mediated cleavage of a “reactive site … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Recombinant proteins were also subjected to trypsin digestion and the resulting tryptic fragments were sequenced by tandem mass spectrometry as reported previously (17).…”
Section: Methodsmentioning
confidence: 99%
“…Recombinant proteins were also subjected to trypsin digestion and the resulting tryptic fragments were sequenced by tandem mass spectrometry as reported previously (17).…”
Section: Methodsmentioning
confidence: 99%
“…It can inhibit cell apoptosis in mammalian, insect, and nemathelminth species, and is a widely effective inhibitor of apoptosis. Research has shown that P35 protein can combine the conserved constituent caspase in the apoptosis pathway and interact with it so as to inhibit its activity (Guy and Friesen, 2008;Brand et al, 2012). In vitro study results have shown that the P35 protein can form a complex that has steric stability with respect to its target molecules and can inhibit the activity of caspase in a competitive binding mode.…”
Section: Discussionmentioning
confidence: 99%
“…Matrix‐assisted laser desorption ionization time‐of‐flight mass spectrometry (MALDI‐TOF MS) was conducted using an Ultraflex III MALDI‐TOF/TOF mass spectrometer controlled by FlexControl software v2.0 (Bruker Daltonics) . The mass spectrum was acquired in linear positive mode and the data were calibrated externally with Bruker's MALDI mass calibration protein standards in the range of 5734–66431 Da (Supporting Information Figure S2).…”
Section: Methodsmentioning
confidence: 99%